From Theory to Policy with Gravitas: A Solution to the Mystery of the Excess Trade Balances - Gabriel J. Felbermayr; Yoto V. Yotov (Center for Economic Studies and ifo Institute (CESifo), 2019)
Bilateral trade balances often play an important role in the international trade policy debate. Academic economists understand that they are misleading indicators of competitiveness and of the gains from trade. However, they also recognize their political relevance, calling for accurate statistical measurement and for more scholarly work. Disturbingly, Davis and Weinstein (2002) argue that the canonical gravity model of trade fails when confronted with bilateral trade balances data, dubbing this “The Mystery of the Excess Trade Balances”. Capitalizing on the latest developments in the theoretical and empirical gravity literature, we demonstrate that the workhorse international trade model actually performs well in explaining bilateral trade balances. Moreover, in our data, only 11 to 13% of the variance in bilateral balances is due to asymmetric bilateral trade costs, belying beliefs that bilateral imbalances are driven by `unfair' manipulation of terms-of-trade. We also perform several general equilibrium experiments within the same structural gravity framework to show that free trade agreements tend to exacerbate bilateral imbalances and that macroeconomic rebalancing leads to adjustment with all trade partners.
Keywords: F10; F13; F14; 330; trade imbalances; structural gravity estimation